2018
DOI: 10.1039/c8cc01003j
|View full text |Cite
|
Sign up to set email alerts
|

Exposed metal oxide active sites on mesoporous titania channels: a promising design for low-temperature selective catalytic reduction of NO with NH3

Abstract: A subtle catalyst design is provided with stably incorporated binary catalytically active centers of CuO and MnO2 on the surface wall of mesoporous TiO2. Such unique features render these mesoporous composites highly promising in the low-temperature selective catalytic reduction of NO with NH3, including high NO conversion efficiency, and superior H2O and SO2 resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…By acetic acid-assisted one-pot method, the metal oxide uniformly dispersed in the channels of ordered mesoporous TiO 2 and exhibited excellent low-temperature NH 3 À SCR performance and the resistance toward H 2 O and SO 2 . [39] Recently, our group reported a spatial confined NH 3 À SCR catalyst by dispersing MnO x À CeO x active component inside the mesochannels of SBA-15 ( Figure 1b, Figure 2b). The confined and highly dispersive active MnÀ Ce oxide species exhibited improved H 2 O and SO 2 resistance and great durability in longterm reaction (72 h) without aggregation.…”
Section: Porous Metal Oxidesmentioning
confidence: 97%
See 1 more Smart Citation
“…By acetic acid-assisted one-pot method, the metal oxide uniformly dispersed in the channels of ordered mesoporous TiO 2 and exhibited excellent low-temperature NH 3 À SCR performance and the resistance toward H 2 O and SO 2 . [39] Recently, our group reported a spatial confined NH 3 À SCR catalyst by dispersing MnO x À CeO x active component inside the mesochannels of SBA-15 ( Figure 1b, Figure 2b). The confined and highly dispersive active MnÀ Ce oxide species exhibited improved H 2 O and SO 2 resistance and great durability in longterm reaction (72 h) without aggregation.…”
Section: Porous Metal Oxidesmentioning
confidence: 97%
“…Our group have exploited the confinement effects of porous oxides to design the NH 3 −SCR catalysts. By acetic acid‐assisted one‐pot method, the metal oxide uniformly dispersed in the channels of ordered mesoporous TiO 2 and exhibited excellent low‐temperature NH 3 −SCR performance and the resistance toward H 2 O and SO 2 [39] . Recently, our group reported a spatial confined NH 3 −SCR catalyst by dispersing MnO x −CeO x active component inside the mesochannels of SBA‐15 (Figure 1b, Figure 2b).…”
Section: The Design Of Spatial Confined Architectures For Nh3−scr Catmentioning
confidence: 99%
“…Their results also revealed that a large amount of nitrate thereby N 2 O being produced over the Fe-Mn/SBA-15 during the reaction due to its strong oxidation ability, low acidity, and high basicity, which resulted in the lower N 2 selectivity [136]. Fan and co-workers [134] fabricated ordered mesoporous titania supported CuO and MnO2 composites (CuO/MnO2-mTiO2) through a facile acetic acid-assisted one-pot synthesis approach, showing high deNOx efficiency (>90% NO conversion) and N2 selectivity (>95%) in a wide operating temperature range of 120-300 °C. They considered that the superior NH3-SCR performance could be attributed to the unique structure and highly integrated mesoporous TiO2 supported by the multicomponent system with high surface areas, accessible and homogenously dispersed CuO and MnO2 with multivalent nature and good redox activity.…”
Section: Supported Binary and Multi Transition Metal-based Catalystsmentioning
confidence: 98%
“…Fan and co-workers [134] fabricated ordered mesoporous titania supported CuO and MnO 2 composites (CuO/MnO 2 -mTiO 2 ) through a facile acetic acid-assisted one-pot synthesis approach, showing high deNO x efficiency (>90% NO conversion) and N 2 selectivity (>95%) in a wide operating temperature range of 120-300 • C. They considered that the superior NH 3 -SCR performance could be attributed to the unique structure and highly integrated mesoporous TiO 2 supported by the multicomponent system with high surface areas, accessible and homogenously dispersed CuO and MnO 2 with multivalent nature and good redox activity. Although the CuO/MnO 2 -mTiO 2 catalyst had good tolerance to H 2 O, the resistance to SO 2 and H 2 O/SO 2 poisoning, as well as high space velocity (GHSV), still need to be enhanced for practical use.…”
Section: Supported Binary and Multi Transition Metal-based Catalystsmentioning
confidence: 99%
“…For example, Yang et al. [ 314 ] successfully constructed a CuO/MnO 2 –TiO 2 ternary semiconductor heterostructure by uniformly loading the well‐crystallized CuO and MnO 2 on the pore wall surface of mesoporous TiO 2 using an acetic acid assisted one‐pot method ( Figure a). The as‐prepared mesoporous composites showed superior catalytic performance for the low‐temperature SCR of NO by NH 3 , high selectivity of N 2 , and excellent H 2 O and SO 2 resistance.…”
Section: Fabrication Of Mno2‐based Compositesmentioning
confidence: 99%